Populism, eco-populism, and the future of environmentalism - Stone, James R. (Routledge research in environmental policy and politics, 2022)
"Populism, Eco-populism, and the Future of Environmentalism analyzes the history and language of populism in order to fully comprehend the threat of eco-fascism - paradoxically revealing that it is possible for there to be both progressive eco-populist and right-wing sham eco-populist discourses. The book highlights the harrowing prospect that the crises of democracy now confronting countries such as the United States may culminate in forms of eco-fascism in a world increasingly divided over issues of economic and social inequality, immigration, and competition for dwindling resources. The author reveals that there is a language of eco-populism that accompanies populist and sham populist discourse of the left and right as ecological crises have assumed a more prominent role in national and global politics.